Analysis of Steam Turbine Coupling Finite Element Method (International Journal of Current Engineering and Technology, 2015)
The manufacturing cost of a component is direction proportional to the difference between the lower and upper specification limits and the functional aspects of the assembly of two components are also affected by the magnitude of fit between those components. In the present work detail, a study of interference fit between coupling and shaft in a steam turbine is carried out. Under normal operating conditions, the coupling hub is expected to transmit 75 MW at the rated speed of 3000 RPM. The interference fit between the motor and turbine to transmit the torque is analyzed by estimating the contact pressure between the coupling and shaft using 2D FEM analysis. The analysis were performed for: (i) Stand-still condition, (ii) Operating at the rated speed with short circuit conditions, equivalent to 4.4 times the nominal power transmission and (iii) Operating at rated torque but higher (121% of the rated) speed conditions. The analysis for each cases is performed by having two different type of meshing (i) uniform meshing and (ii) fine meshing at the contact zone and (i) contact pressure, (ii) Tangential stress distribution and (iii)Von-mises stress is estimated. The validation of FEM method was performed by comparing the theoretical and estimated reduction in contact pressure. The maximum value of power developed for the present case is estimated.
Keywords: FEM; Interference Fit; Contact pressure